2020
DOI: 10.1128/jcm.02162-20
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein Testing for Active Tuberculosis among Inpatients without HIV in Uganda: a Diagnostic Accuracy Study

Abstract: Setting: National referral hospital in Kampala, Uganda Objective: To determine diagnostic performance of serum C-reactive protein (CRP) as a triage test for tuberculosis (TB) among HIV-seronegative inpatients. Design: Prospective cross-sectional study. We calculated sensitivity, specificity, positive and negative likelihood ratios, and positive and negative predictive values to determine the diagnostic performance of a CRP ELISA assay (Eurolyser), in comparison to a reference standard of Mycobacterium tubercul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 33 publications
1
13
1
1
Order By: Relevance
“…Similar results were observed in other studies in which the combination of CRP and other biomarkers showed superior performance for TB identification (18,19). However, a recent diagnostic accuracy study excluded the utility of CRP as a TB triage test due to its low specificity (20). Therefore, additional studies are still needed to assess the utility of CRP for TB screening, especially in TAK patients.…”
Section: Discussionsupporting
confidence: 83%
“…Similar results were observed in other studies in which the combination of CRP and other biomarkers showed superior performance for TB identification (18,19). However, a recent diagnostic accuracy study excluded the utility of CRP as a TB triage test due to its low specificity (20). Therefore, additional studies are still needed to assess the utility of CRP for TB screening, especially in TAK patients.…”
Section: Discussionsupporting
confidence: 83%
“…High accuracy has been reported in some studies of HIV co-infected patients [ 21 , 22 ], though there have been fewer studies assessing screening among HIV-negative individuals, and performance has generally been poorer. A recent study among HIV-negative inpatients in Uganda found specificity of 21% at sensitivity of 91% [23] . We are unaware of any studies assessing C-reactive protein in the context of mass screening for active case detection.…”
Section: Discussionmentioning
confidence: 95%
“…A recent study among HIV-negative inpatients in Uganda found specificity of 21% at sensitivity of 91%. 23 We are unaware of any studies assessing C-reactive protein in the context of mass screening for active case detection. We found the AUC to be 0.79 for the point-of-care CRP test in our study, consistent with the moderate accuracy previously reported in HIV-uninfected individuals.…”
Section: Discussionmentioning
confidence: 99%